A COMPARATIVE ANALYSIS OF SPORTS PARTICIPATION AS A RELAXATION ACTIVITY VERSUS A DEVELOPMENT PROFESSION: A QUANTITATIVE CROSS-SECTIONAL STUDY - Dr Uzma Munawar; Husna Nazeer; Marium Hussain (International Journal of Contemporary Issues in Social Sciences, 2024)
This study provides a comparative analysis of sports participation as a leisure activity versus its role as a development profession, with a specific focus on gender differences. Using a quantitative cross-sectional design, data were collected from 60 participants 30 males and 30 females who were involved in sports either recreationally or professionally. Key variables such as physical and psychological well-being, social integration, and skill development were measured and analyzed to identify significant differences between the groups.The quantitative analysis was utilizing a cross-sectional survey design to assess the motivations, participation rates, and barriers to sports participation among leisure sports participants and professional athletes. This approach allows for the collection of data at a single point in time, facilitating comparisons between the two groups.The results indicate that both male and female participants benefit from sports participation, but the nature of these benefits varies depending on whether the activity is pursued as a leisure pastime or a professional career. Male participants involved in professional sports reported higher levels of skill acquisition and career satisfaction but also faced greater stress and pressure. Female professionals exhibited similar patterns but reported slightly higher levels of psychological stress compared to their male counterparts. The study concludes that sports participation offers distinct advantages depending on gender and the nature of involvement either as a leisure activity or a professional pursuit. These findings can guide the development of gender-sensitive sports programs and policies that cater to the specific needs and goals of different populations.